Désambiguïsation des sens du prédicat adjectival farouche dans le cadre d’une approche orientée objets - Hrabia, Michał (Neophilologica, 2011)
This article examines the French adjective farouche with the aim of disambiguating all its meanings. The methodology of this study is based on the object-oriented approach proposed by W. Banyś. The author seeks to find all the Polish equivalents of the word analyzed. The choice of equivalents is determined by the configuration of the object classes qualified by farouche and, possibly, by the frames in which the adjective in question appears. The results of the analysis are presented in the syntactic-semantic schemes with the contexts found in different databases (monolingual dictionaries, the Internet) and in the summary table. Finally, the author discusses the problem of the proper nouns qualified by farouche.